2003
DOI: 10.1243/09544110360579330
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamic pressure profiles of a patellar-tendon-bearing (PTB) socket

Abstract: The purpose of this study was to evaluate the pressure distribution at the stump/socket interface in amputees wearing the patellar-tendon-bearing socket. A specially built strain gauged type pressure transducer was used for measuring this pressure distribution in four unilateral transtibial amputees. Pressure and gait parameters were measured simultaneously while they were standing and walking. Pressure profiles were compiled at 10, 25 and 50 per cent of gait cycle and compared with the pressure profiles predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 5 publications
1
8
1
Order By: Relevance
“…However, the profiles observed for the sockets instrumented by Goh et al indicated a large difference in the distribution of pressure over the anterior aspect at late stance [24][25], which was not replicated in our study. We should note that the pressure profiles described by Radcliffe were based on normal walking patterns [23], while the profiles given by Goh et al were recorded when the subjects were not wearing an interface liner [24][25].…”
Section: Profile Over Anterior and Posterior Aspects Of Socketcontrasting
confidence: 96%
See 1 more Smart Citation
“…However, the profiles observed for the sockets instrumented by Goh et al indicated a large difference in the distribution of pressure over the anterior aspect at late stance [24][25], which was not replicated in our study. We should note that the pressure profiles described by Radcliffe were based on normal walking patterns [23], while the profiles given by Goh et al were recorded when the subjects were not wearing an interface liner [24][25].…”
Section: Profile Over Anterior and Posterior Aspects Of Socketcontrasting
confidence: 96%
“…The pressure profiles measured for both the hands-on and hands-off concepts indicated that on average, the interface pressure showed the greatest change between mid stance and late stance (p < 0.001 for both socket concepts). This contradiction concurs with two other investigations into the profile of interface pressure [24][25].…”
Section: Distribution Of Interface Pressuresupporting
confidence: 91%
“…Thereafter, several researchers improved the SG-based in-socket-wall transducer designs which contributed to better understanding of interface stresses in transtibial prosthetic sockets [ 11 , 16 , 79 , 80 ]. Clinical investigations of normal and shear stresses that involve a number of amputees were then conducted during standing and walking [ 44 , 80 , 81 , 82 , 83 ].…”
Section: Types Of Transducersmentioning
confidence: 99%
“…He claimed that in most cases, the traditional concept of load transfer to areas such as the patellar tendon, medial flare and condyles of the tibia, is ineffective and uncomfortable. A number of investigators [4][5][6][7][8][9][10][11][12][13] have shown that the pressures within the PTB socket are, as expected, not uniformly distributed. In general, peak pressures taken from walking subjects yield values of around 300 kPa recorded at the site of the patellar tendon bar.…”
Section: Introductionmentioning
confidence: 86%